MOTIVATION TO SEA AMONG YOUTH (Case Study of Millennial Youth in the North Galesong Coastal Community, Takalar Regency) - Lambe, Kristian Hoegh Pride; Radjab, Mansyur; Hasbi, Hasbi; Sabiq, Muhammad (Agrikan: Jurnal Agribisnis Perikanan, 2021)
This study examines the motivation to go to sea among youth, North Galesong. The research method used is a qualitative case study type. Sources of data in this study are divided into two kinds of categories, namely primary and secondary sources. Data collection techniques used are interviews, observation and documentation. The results showed that the motivation of youth to become fishermen comes from intrinsic motivation and extrinsic motivation. Intrinsic motivation is obtained from within the individual with conscious considerations such as an understanding of the economic potential of their area, an understanding of technology and an understanding of fishing skills. While the external motivation is obtained from outside the youth, such as the pressure to fulfill economic needs, support and even coercion from the family